Belize : 2022 Article IV Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2022)
The COVID-19 pandemic had a severe impact on Belize in 2020, leading to a 16.7 percent contraction in real GDP and a rise in public debt to an unsustainable level of 133 percent of GDP. To address this situation, the government presented a medium-term plan to lower public debt to 85 percent of GDP in 2025 and 70 percent in 2030 by implementing fiscal consolidation, structural reforms, and debt restructuring. Significant progress towards restoring debt sustainability was made in 2021.